2023
DOI: 10.3390/children10020295
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Acute Chemical Poisoning among Children over a Recent Three-Year Period in Saudi Arabia

Abstract: Acute intoxication from chemicals is a major medical emergency that can result in illness and mortality. This retrospective study aims to evaluate acute chemical poisoning incidents among children in Saudi Arabia from 2019 to 2021. A total of 3009 children were recorded as being chemically intoxicated. The SPSS/PC statistics package was used for the statistical analysis. The acute chemical poisoning incidents that occurred in the age groups were <1 year: 237 (7.8%), 1–5 years: 2301 (76.4%), 6–12 years: 214 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The study showed that one in every 25 children hospitalised at a large tertiary-level hospital in South Africa are poisoned, a third from organic solvents (such as paraffin) and medications, respectively, and alarmingly a further 18% from pesticides. Furthermore, 56 (2.1%) children demised from poisoning which is four-fold higher than the 0.5% reported in high-income countries (13). The mortality rate for children with pesticide poisoning was also more than double in the study.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The study showed that one in every 25 children hospitalised at a large tertiary-level hospital in South Africa are poisoned, a third from organic solvents (such as paraffin) and medications, respectively, and alarmingly a further 18% from pesticides. Furthermore, 56 (2.1%) children demised from poisoning which is four-fold higher than the 0.5% reported in high-income countries (13). The mortality rate for children with pesticide poisoning was also more than double in the study.…”
Section: Discussionmentioning
confidence: 50%
“…In our study, pesticides, including organophosphates were a common (18%) cause of poisoning. Ingestion of pesticides may occur accidentally in young children who have an increased hand to mouth activity and exploring their surroundings -this is particularly relevant in our setting where these pesticides are used to curb rodent infestation (6,13). Pesticides could also be used for intentional poisoning, particularly among adolescents (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation